Plague writing in early modern England - Gilman, Ernest B. (University of Chicago Press, 2009)
During the 17th century, England was beset by three epidemics of the bubonic plague, each outbreak claiming between a quarter and a third of the population of London and other urban centres. This book brings to life the many and complex ways Londoners made sense of such unspeakable devastation.
10.7208/chicago/9780226294117.001.0001/upso-9780226294094
Keywords: Englisch; Literatur; Pest; English literature; Diseases and literature; Plague in literature; Epidemics in literature; Diseases in literature; Plague; Epidemics; Literature and society